Correction: Chang et al. Fabrication of Stromal Cell-Derived Factor-1 Contained in Gelatin/Hyaluronate Copolymer Mixed with Hydroxyapatite for Use in Traumatic Bone Defects. Micromachines 2021, 12, 822 - Yun-Liang Chang; Chia-Ying Hsieh; Chao-Yuan Yeh; Chih-Hao Chang; Feng-Huei Lin (Micromachines)
The authors wish to make a change to the published paper [...]